Formation of giant gold provinces by subduction-induced reactivation of fossilized, metasomatized continental lithospheric mantle in the North China Craton - Xiong, Le; Zhao, Xinfu; Zhao, Shaorui; Lin, Haitao; Lin, Zuwei; Zhu, Zhaoxian; Wang, Zaicong; Li, Martin Yan Hei; Li, Jianwei (Chemical geology, 2021)
Subcontinental lithospheric mantle (SCLM) metasomatized by recycled components from oceanic subduction zone constitutes a fertile source for some of world's most important hydrothermal Au-rich ore systems. However, a widely recognized time gap exists between subduction initiation, regional contraction, and Au-ore formation at continental edges, which makes it unclear when and how the subduction and orogenic processes contributed to the ore formation. The North China craton (NCC) hosts giant Mesozoic lode gold deposits at its edge and has undergone multistage subduction history, which provides an ideal opportunity to illustrate this issue. Here we present a comprehensive lead isotope study on major Early Cretaceous lode gold deposits of the NCC and show that the gold was derived from a metasomatized SCLM rather than the crustal basement. Furthermore, the data shows that subduction of the (paleo-) Pacific did not likely provide significant amount of metals for the contemporaneous gold mineralization during the Early Cretaceous. Instead, the gold was most likely derived from the SCLM underlying the NCC, previously fertilized by the sedimentary sequences overlying the Yangtze craton during Early Paleozoic to Early Mesozoic subduction. This study emphasizes the fundamental role of the metasomatized SCLM in the formation of lode gold deposits in the NCC, and possibly other Au-rich ore systems worldwide, and explains the close, temporal relations between tectonic extension and the formation of Au-rich ore systems.